EL PATRONZAGO ARTÍSTICO DEL AYUNTAMIENTO DE CARTAGENA EN EL SIGLO XVI Y PRINCIPIOS DEL XVII - Montojo Montojo, Vicente (Imafronte, 1993)
The artistic patronage of the Cartagena City Council was devoted, amotig other issuas, to stand out the social preeminetice of the institution and its members; this provoked sonic. suspicion in certain social sectors of the city. We study, from un artistic view, several action ambits of the Council. such as the Main Chapel of the Parish Church of the Assumption, remodeled in 1555, ring the Chapel of the City Hall, the reredos of which was made by Artus de Brant in 1575. Finally, we point out the attraction originated by the artistic activity in the city, which got several painters to settle down definitively in Cartagena (among them, Salustio Lucas and Francisco de Aguilar, in 1600-1620).